2021
DOI: 10.1016/j.isci.2021.102278
|View full text |Cite
|
Sign up to set email alerts
|

Twinning-mediated anomalous alignment of rutile films revealed by synchrotron X-ray nanodiffraction

Abstract: Summary Nanotwin structures in materials engender fascinating exotic properties. However, twinning usually alter the crystal orientation, resulting in random orientation and limited performances. Here, we report a well-aligned rutile TiO 2 nanotwin film with superior preferential orientation than its isostructural substrate. By means of the synchrotron X-ray Laue nanodiffraction technique, the crystal orientation, twin boundaries, and deviatoric stresses of the film were quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Furthermore, the sodium-decorated amorphous/crystalline RuO 2 (a/c-RuO 2 ) interface containing rich oxygen vacancies (V O s) was developed as an excellent pH-universal OER electrocatalyst, showing remarkable resistance to acid corrosion and oxidation during the OER . The short-range disordered structure at the interface introduces abundant unsaturated bonds and V O s. In fact, high-resolution transmission electron microscopy images revealed that a large number of twin structures and point defects can be observed in the distortion region, showing obvious local disorder characteristics. , Thus, due to the characteristics of short-range disorder and long-range order, local amorphous structures could be simulated by introducing nanotwins with point defects, which constructed the characteristic structure combining local lattice distortion and unsaturated bonds. The nanotwins could not be ignored when investigating the OER reaction mechanism .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the sodium-decorated amorphous/crystalline RuO 2 (a/c-RuO 2 ) interface containing rich oxygen vacancies (V O s) was developed as an excellent pH-universal OER electrocatalyst, showing remarkable resistance to acid corrosion and oxidation during the OER . The short-range disordered structure at the interface introduces abundant unsaturated bonds and V O s. In fact, high-resolution transmission electron microscopy images revealed that a large number of twin structures and point defects can be observed in the distortion region, showing obvious local disorder characteristics. , Thus, due to the characteristics of short-range disorder and long-range order, local amorphous structures could be simulated by introducing nanotwins with point defects, which constructed the characteristic structure combining local lattice distortion and unsaturated bonds. The nanotwins could not be ignored when investigating the OER reaction mechanism .…”
Section: Introductionmentioning
confidence: 99%